Pleuroparenchymal fibroelastosis-like lesions in patients with interstitial pneumonia diagnosed by multidisciplinary discussion with surgical lung biopsy. (2020) - Sumikawa, Hiromitsu; Johkoh, Takeshi; Egashira, Ryoko; Sugiura, Hiroaki; Yamano, Yasuhiko; Kataoka, Kensuke; Kondoh, Yasuhiro; Arakawa, Hiroaki; Nakamura, Masahisa; Kuriu, Akihiro; Nakanishi, Katsuyuki; Tomiyama, Noriyuki
Abstract: Purpose: The present study aimed to evaluate the significance of Pleuroparenchymal fibroelastosis (PPFE)-like lesions in predicting prognosis in patients with chronic interstitial pneumonia (IP). Method: The present study enrolled 207 patients with IP in whom surgical lung biopsy was performed. Among the patients enrolled in the present study, 77 had idiopathic pulmonary fibrosis (IPF), 15 had nonspecific interstitial pneumonia (NSIP), 13 had chronic hypersensitivity pneumonitis (CHP), 41 had connective tissue disease (CTD), three had PPFE, and 58 had unclassifiable diagnosis. The incidence, characteristics, and thickness of PPFE-like lesions were evaluated in each patient with IP. Additionally, the influence of PPFE-like lesions on the prognosis was also determined. Results: Of 207 patients, 160 (77.3 %) showed PPFE-like lesions. The frequency of PPFE-like lesions was similar in patients with IPF, NSIP, CHP, CTD, and unclassifiable diagnosis (79.5 %, 79.5 %, 73.2 %, 65.9 %, and 81 %, respectively); however, PPFE-like lesions were present in all patients with PPFE (p = 0.42). Consequently, there was no significant difference in the characteristics of PPFE-like lesions among patients with all forms of IP, except PPFE. PPFE-like lesions were not a significant predictor of prognosis (hazard ratio [HR], 1.16; 95 % confidence interval [CI], 0.64–2.10, p = 0.62); however, patients with PPFE-like lesions under the aortic arch had significantly poorer prognoses (HR, 2.70; 95 % CI, 1.66–4.39, p < 0.001). For craniocaudal extent comparison, patients with IPF with PPFE-like lesions below the level of the carina had significantly poorer prognoses than those without PPFE-like lesions (p = 0.001, overall survival 53.1 and 80.6, respectively). Conclusion: PPFE-like lesions are common in patients with IP, and their characteristics were not significantly different among all forms of IP, except idiopathic PPFE. The broad extent of PPFE-like lesions is an important predictor of prognosis in patients with IPF.